Renormalization-group calculation of excitation properties for impurity models - Yoshida, M. [UNESP]; Whitaker, M. A.; Oliveira, L. N. (American Physical Society (APS), 1990)
The renormalization-group method developed by Wilson to calculate thermodynamical properties of dilute magnetic alloys is generalized to allow the calculation of dynamical properties of many-body impurity Hamiltonians. As a simple illustration, the impurity spectral density for the resonant-level model (i.e., the U=0 Anderson model) is computed. As a second illustration, for the same model, the longitudinal relaxation rate for a nuclear spin coupled to the impurity is calculated as a function of temperature. © 1990 The American Physical Society.